Pengaruh Karakteristik CEO terhadap Tingkat Performa Corporate Social Responsibility (CSR) Perusahaan di Indonesia - Matthew Alexander Nathaniel; Stephanie Jessica Nadine; Retno Yuliati; Vania Pradipta Gunawan (Jurnal Akuntansi, 2020)
This study aims to examine the relationship between the Chief Executive Officer (CEO)’s characteristics and the performance of corporate social responsibility (CSR). Using a sample of Indonesian companies listed on the Indonesia Stock Exchange (IDX) for the 2013 - 2017 period. Also our study limits the number of samples by only examining companies that have ESG assessment results based on Bloomberg data and eliminates financial company. We found that 65 companies had ESG assessment in the period of 5 years. This study directly addresses this issue by using multiple regression to test these two relationships. We found that CEO’s work experience has a positive and significant relationship to the company's CSR performance. A negative and significant relationship to the company's CSR performance were found in the CEO’s tenure, female CEO and CEO with economics / accounting / business educational background. We found that CEO’s age have no relationship to the company’s CSR performance. This study provides contribution to previous research, that the Upper Echelon theory can explain the relationship between CEO characteristics and the company’s CSR performance.